2011
DOI: 10.1111/j.1365-2702.2010.03607.x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Impact of Event Scale (IES): version for Brazilian burn victims

Abstract: The Impact of Event Scale can be used in research and clinical practice to assess nursing interventions aimed at decreasing stress during rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The IES was validated for Brazilian Portuguese by Echevarria‐Guanilo et al . (), with Cronbach's alphas of 0·87 for intrusion, 0·76 for avoidance and 0·87 for the total scale.…”
Section: The Studymentioning
confidence: 99%
“…The IES was validated for Brazilian Portuguese by Echevarria‐Guanilo et al . (), with Cronbach's alphas of 0·87 for intrusion, 0·76 for avoidance and 0·87 for the total scale.…”
Section: The Studymentioning
confidence: 99%
“…A score of 33 or higher has been suggested to be indicative of a PTSD diagnosis (Creamer, Bell, & Failla, 2003). The IES‐R has been used with many international samples, showing convergent validity with depression (Echevarria‐Guanilo et al, 2011) and PTSD (Lim et al, 2009), and has found support for the three‐factor solution in a U.S. sample (Beck et al, 2008). The IES‐R has also been used with a variety of samples and demonstrated strong reliability (e.g., α = .94; Okello, Nakimuli‐Mpungu, Musisi, Broekaert, & Derluyn, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Total scores range from 10 to 40 points, higher scores indicating more self-esteem [ 22 ]. RSES has been used in previous studies with Brazilian burn patients [ 21 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The potential range of the BDI is 0 to 63, with higher scores reflecting more depressive symptoms [ 25 ]. The BDI has also been used in other studies with Brazilian burn patients [ 21 , 23 ].…”
Section: Methodsmentioning
confidence: 99%